2014
DOI: 10.1038/ncomms4022
|View full text |Cite
|
Sign up to set email alerts
|

Spiracular air breathing in polypterid fishes and its implications for aerial respiration in stem tetrapods

Abstract: The polypterids (bichirs and ropefish) are extant basal actinopterygian (ray-finned) fishes that breathe air and share similarities with extant lobe-finned sarcopterygians (lungfishes and tetrapods) in lung structure. They are also similar to some fossil sarcopterygians, including stem tetrapods, in having large paired openings (spiracles) on top of their head. The role of spiracles in polypterid respiration has been unclear, with early reports suggesting that polypterids could inhale air through the spiracles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 25 publications
1
58
0
1
Order By: Relevance
“…In this group and later taxa, there was an enlargement of breathing spiracles (also called otic notches) located behind the eyes (green in Fig. 5) (9,13,26,40). The enlargement of spiracles occurred during a time of Earth's history when oxygen levels trended downward (26,41).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this group and later taxa, there was an enlargement of breathing spiracles (also called otic notches) located behind the eyes (green in Fig. 5) (9,13,26,40). The enlargement of spiracles occurred during a time of Earth's history when oxygen levels trended downward (26,41).…”
Section: Discussionmentioning
confidence: 87%
“…It has been suggested that the anatomical features of the elpistostegalians-enlarged breathing spiracles at the top of the skull and eyes on top of the skull on bony prominences-enabled stealthy crocodilian-like predatory behavior (8,13,40), in which animals are at the surface with their eyes and spiracles just out of the water, looking at the water-land interface for potential prey to attack from the water (Tiktaalik in Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Lungs, as a ventral derivate, are considered as plesiomorphic for osteichthyans [11,13], as they are found in the extant basal actinopterygian polypterids [1416], and in all major groups of extant sarcopterygians: coelacanths [17,18], lungfishes [1,1921] and tetrapods.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, as the stapes has a concave and rough distal end, the otic notch is presumed to be partially covered by soft tissue or by a spiracle valve, as in Polypterus (Graham et al 2014). …”
Section: Role Of the Stapesmentioning
confidence: 99%